The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.destud.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Refinements to the variety metric for idea evaluation

Abstract: Systematically developing innovative products demands effective idea generation methods. The effectiveness can be verified based on a set of metrics, of which the variety metric is one. It is demonstrated that this metric exhibits several shortcomings, such as the lack of level-based measurements, and arbitrarily defined level weights. The currently applied variety metrics, furthermore, do not measure the degree of uniformness of the distribution of ideas over nodes on an abstraction level. A level-based, corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…An overview of the different approaches to variety calculation is offered by Verhaegen, Vandevenne, Peeters, and Duflou (2013); who propose two main refinements to the state-of-the-art. First, a level-based variety score is detailed to allow the evaluation of the idea set on each abstraction level in the genealogy tree.…”
Section: Varietymentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the different approaches to variety calculation is offered by Verhaegen, Vandevenne, Peeters, and Duflou (2013); who propose two main refinements to the state-of-the-art. First, a level-based variety score is detailed to allow the evaluation of the idea set on each abstraction level in the genealogy tree.…”
Section: Varietymentioning
confidence: 99%
“…Hereby information is reported that potentially is lost when using an aggregated variety metric. Furthermore, Verhaegen et al (2013) propose a refinement to the variety metric that takes into account the uniformity of the distribution of ideas. By integrating the inverse of the Herfindahl index (Herfindahl, 1950), the new proposed variety calculation demonstrates a more gradual behaviour and avoids overestimation of the actual variety of the idea set.…”
Section: Varietymentioning
confidence: 99%
“…Nelson, Wilson, Rosen, & Yen, 2009;Verhaegen et al, 2013). However, such refinements have not yet been proposed to Sarkar and Chakrabarti's novelty assessment method despite deficiencies in it.…”
Section: Introductionmentioning
confidence: 99%
“…Creativity, a fundamental aspect of human intelligence, is important in designing products (Cross, 2011;Gerber & Martin, 2012;Verhaegen, Vandevenne, Peeters, & Duflou, 2013) and supporting companies to capture large market share (Eisentraut & Badke-Schaub, 1995). It is highly related to the commercial performance of businesses (Childs & Fountain, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated ways of collaboration to help further elaborate ideas (e.g., Chen, Chuy, Resendes, Scardamalia, & Bereiter, 2011;Kipp, Bittner, Bretschneider, & Marco, 2014) and ways of idea elaboration that may enhance or hinder creative knowledge work (e.g., Kudrowitz & Wallace, 2013;Stark & Perfect, 2008;Verhaegen, Vandevenne, Peeters, & Duflou, 2013). For example, Kudrowitz and Wallace's (2013) study found that the systematic use of a metric integrating three attributes (i.e., novelty, usefulness, and feasibility) as an elaboration means can be helpful in identifying more innovative ideas.…”
Section: Fostering the Process Of Idea Improvementmentioning
confidence: 99%